The role of social responsibility accounting in achieving sustainable development: The case of major industrial groups in Algeria - Habib, Marouf; Kahina, Chaouchi; Ines, Siouda; Amina, Kedaifa; Mohammed, Grinat (The International tax journal, 2025)
This study aims to examine the impact of social responsibility accounting on sustainable development in major industrial groups in Algeria. To achieve this objective, 125 questionnaires were distributed to a random sample of financial and accounting managers in large industrial units representing these groups and their branches. A total of 98 valid responses were obtained for analysis using the statistical software (SPSS.25), based on the descriptive analytical method and the inductive approach. The study found a statistically significant impact of social responsibility accounting when it comes to social accounting measurement, whereas no significant effect was found regarding the second dimension social accounting disclosure at a significance level of 0.05.